Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00590-012-1019-7
|View full text |Cite
|
Sign up to set email alerts
|

Accessory soleus muscle: a difficult diagnosis: a case report and a review of the literature

Abstract: In this article, we report the case of a patient with a symptomatic accessory soleus muscle with an atypical clinical presentation. As the existence of this accessory muscle went unrecognized for a long time, various diagnoses of the patient's condition were made. Initially, the patient was treated for muscle strain and compartment syndrome, but the second MRI revealed the accessory muscle and led to appropriate diagnosis and surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…A significant increase in intensity and exercise workload, in some cases, may lead to pain and disability. These findings are also in agreement with the literature [170].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A significant increase in intensity and exercise workload, in some cases, may lead to pain and disability. These findings are also in agreement with the literature [170].…”
Section: Discussionsupporting
confidence: 94%
“…A summary of the types of manuscripts included in this review is shown in Table 3. Noncomparative studies including opinion pieces/narrative reviews accounted for 45.4% of the included manuscripts [4, 6, 33–84], case reports (22%) [7, 85–109], and case series studies (17%) [110–129]. Five percent of the included manuscripts were systematic reviews [5, 130–134].…”
Section: Resultsmentioning
confidence: 99%
“…As it may mimic a soft tissue tumor, it is essential to differentiate this condition from ganglion, lipoma, hemangioma, synovioma, and sarcoma [ 5 ]. ASM may also present with a painful syndrome, characterized by pain and paresthesia of the ankle and foot, mimicking the tarsal tunnel syndrome (TTS) [ 6 ]. Here, we report on two symptomatic cases of ASM, one with a typical presentation and treatment protocol and one with an atypical presentation, which led to delayed diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%